AHP and TOPSIS applied in the field of scientific research - Mohamed El Mohadab; Belaid Bouikhalene; Fahd Ouatik; Said Safi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Scientific research is a major issue for universities because it ensures its innovation and productivity, but to ensure the proper functioning of universities, the decisions-makers need powerful tools to assist them in this process. Multi criteria decision making (MCDM) may present an appropriate asset for this area especially with the analytical hierarchy process (AHP) which presents a theory of measurement through pairwise comparisons and relies on the judgments of experts to derive priority scales.